Proceedings of the 2019 Conference of the North 2019
DOI: 10.18653/v1/n19-1115
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Learning of Disjoint Syntax and Semantics

Abstract: There has been considerable attention devoted to models that learn to jointly infer an expression's syntactic structure and its semantics. Yet, Nangia and Bowman (2018) has recently shown that the current best systems fail to learn the correct parsing strategy on mathematical expressions generated from a simple context-free grammar. In this work, we present a recursive model inspired by Choi et al. (2018) that reaches near perfect accuracy on this task. Our model is composed of two separated modules for syntax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 28 publications
(34 reference statements)
1
46
0
Order By: Relevance
“…In other words, it is not capable of compositional learning. One possible route to alleviate this problem could include separating syntax and semantics as is customary on formal semantic methods (Partee et al, 1990) and, as recently suggested in the context of latent tree learning (Havrylov et al, 2019), so that syntax can guide semantics both in processing and learning.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, it is not capable of compositional learning. One possible route to alleviate this problem could include separating syntax and semantics as is customary on formal semantic methods (Partee et al, 1990) and, as recently suggested in the context of latent tree learning (Havrylov et al, 2019), so that syntax can guide semantics both in processing and learning.…”
Section: Discussionmentioning
confidence: 99%
“…This will be even more of a problem if we would attempt to use it in the joint learning setup. Also note that similar parsing models do not yield linguistically-plausible structures when used in the conventional (i.e., non-grounded) grammarinduction set-ups (Williams et al, 2018;Havrylov et al, 2019).…”
Section: Limitations Of the Vg-nsl Frameworkmentioning
confidence: 99%
“…An established method is the score function estimator (SFE) (Glynn, 1990;Williams, 1992;Kleijnen and Rubinstein, 1996). SFE is widely used in NLP, for tasks including minimum risk training in NMT (Shen et al, 2016;Wu et al, 2018) and latent linguistic structure learning Havrylov et al, 2019). In this paper, we focus on the alternative strategy of surrogate gradients, which allows learning in deterministic graphs with discrete, argmax-like nodes, rather than in stochastic graphs.…”
Section: Related Workmentioning
confidence: 99%